The European Institutions and the European Identity - Apostolovska-Stepanoska, Milena; Runcheva Tasev, Hristina (Helenic American University, Athens, 2016)
The author in this article divides the research in two parts. The first part of the article is devoted on the European identity issue and here the author claims that the European identity can be build and that the European institutions have very important role in this process. Namely, the European institutions affect the European identity when they are developing politics working regarding their competencies. The theoretical frame and the main hypothesis of this article is given by the theory of social constructivism whose developer Thomas Risse says that the European political identity can be created and changed and that the politics brought by the institutions are one of the mechanisms for that purpose. In that direction the author of this article says that the European citizenship that was introduced with the Treaty of Maastricht is one of the attempts of the institutions of the European Union to crate feeling of belonging to the supranational organization to the citizens of the member states. In order to proof its claim the authors of the article make short analysis of the development of the rights that were introduced with the Treaty of Maastricht and compare how they evolve in every Treaty after. Furthermore the authors make preview of the most important decisions, regulations, directives, reports, declarations and proposals that were brought by the European Parliament, the European Commission, the Council and the European Council regarding the rights and obligations that the European citizens obtain with the European citizenship and in that manner influence on the creation of the European identity. In the second part of the article the author deals with the problem of the democratic deficit in the European Union. The paper presents short analysis of this issue that ends with explanation why creating the European identity is a solution for the democartic deficit of the Union
Keywords: European identity, european citizenship, democratic deficit